THE PRESENCE OF ROMA LIFE'S EXPERIENCES, TRADITIONS AND HISTORY IN THE ROMANIAN TEXTBOOKS - A CONTENT ANALYSIS FROM A SOCIAL JUSTICE PERSPECTIVE - Cristina TUNEGARU (National Centre for Policy and Evaluation in Education, 2020)
Roma people have been victims of oppression in Romania for many centuries, "in the long course of the Gypsy experience in Eastern Europe, none has been worse than that in Romania" (Crowe & Kolsti, 1991, p. 61). Nowadays, education can play a key role in assuring that the Roma are treated with respect and dignity, in assuring that they receive recognition, while dismantling the stigma. This paper is the outcome of a study of the representation of minority students in Romanian textbooks. While many educational reforms were targeted to increase Roma students' attendance and results - schools with Roma language teaching, textbooks in Roma native language, affirmative actions for high school and university students of Roma origin - it's an open question as to whether the Romanian textbooks are sufficiently inclusive and effective in combating racial discrimination and stereotyping. By employing a social justice perspective, I argue that textbooks systematically discriminate against Roma children by under- and misrepresenting the Roma experiences, traditions and history. My argument unfolds through two main directions from the data analysis. Firstly, we examine primary and middle school (2nd grade - 6th grade) textbooks in search for representations of Roma realities and culture. Secondly, we explore the presentation or absence of historical facts regarding Roma. This exploratory study hopes to become a starting point for a discussion about applied curriculum in Romania, specifically the textbook component. Limited comparative data was collected and stark differences can be inferred between the attention devoted to Hungarian culture and realities versus the Roma, but further research is warranted.